The guidelines for clinical practice for carriers of germline mutations in hereditary breast, ovarian, prostate, and pancreatic cancer predisposition genes BRCA1, BRCA2, PALB2, ATM, and CHEK2 (4.2024) - Kleiblová, P; Novotný, J; Cibula, D; Curtisová, V; Dubová, O; Foretová, L; Germanová, A; Janatová, M; Havránek, O; Hojsáková, M; Hudcová, M; Koudová, M; et al. (Klinicka onkologie, 2024)
The Guidelines for Clinical Practice for carriers of pathogenic variants in clinically relevant cancer predisposition genes define the steps of primary and secondary prevention that should be provided to these individuals at high risk of developing hereditary cancer in the Czech Republic. The drafting of the guidelines was organized by the Oncogenetics Working Group of the Society for Medical Genetics and Genomics of J. E. Purkyně Czech Medical Society (SLG ČLS JEP) in cooperation with the representatives of oncology and oncogynecology. The guidelines are based on the current recommendations of the National Comprehensive Cancer Network (NCCN), European Society of Medical Oncology (ESMO) and take into account the capacity of the Czech healthcare system.
Keywords: Male; nádory slinivky břišní; nádory prsu; Prostatic Neoplasms; guidelines for clinical practice; CHEK2; Ataxia Telangiectasia Mutated Proteins; BRCA1 Protein; BRCA1; Humans; Checkpoint Kinase 2; Pancreatic Neoplasms; protein FANCN; checkpoint kinasa 2; Česká republika; mužské pohlaví; Czech Republic; Female; BRCA2; zárodečné mutace; ATM protein; ženské pohlaví; germline mutation carriers; ATM; consensus; Genetic Predisposition to Disease; Germ-Line Mutation; směrnice pro lékařskou praxi jako téma; protein BRCA1; nádory prostaty; PALB2; Practice Guidelines as Topic; BRCA2 Protein; Fanconi Anemia Complementation Group N Protein; genetická predispozice k nemoci; lidé; nádory vaječníků; Breast Neoplasms; Ovarian Neoplasms; protein BRCA2